The Category of ‘Unfairness’ in the Contract System Legislation in Russia and the USA: Some Interpretation Issues - MUSABIROVA, Dinara Anvarovna; HAMITOV, Radik Nakimovich (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
This article presents and defines the concept and the criteria for the content of the ‘unfairness’ category as a special evaluation concept, widely used in the legislation to satisfy the public needs in the Russian Federation and other countries, particularly in the USA. The clarification of its nature is of great importance for the application of this legal category in the law-making and law enforcement activities, first of all, to maximize the effectiveness of the legal regulations and compliance with the principle of fair competition in the negotiation and execution of contracts to meet the public needs. The features of the definition of ‘the register of unfair suppliers’ category and a similar institution in the contract system rules of the USA (the ‘unfair trade practices’) were defined. The theoretical studies of the scientists in this field, as well as the recent case law of Russia, are presented and analyzed. It is proposed to reform the Federal Law of the Russian Federation on the contract system.